A novel multifunctional haplotyping-based preimplantation genetic testing for different genetic conditions. Issue 11 (6th September 2022) - Xie, Pingyuan; Hu, Xiao; Kong, Lingyin; Mao, Yan; Cheng, Dehua; Kang, Kai; Dai, Jing; Zhao, Dingding; Zhang, Yi; Lu, Naru; Wan, Zhenxing; Du, Renqian; et al.
Abstract: STUDY QUESTION: Is there an efficient and cost-effective detection platform for different genetic conditions about embryos? SUMMARY ANSWER: A multifunctional haplotyping-based preimplantation genetic testing platform was provided for detecting different genetic conditions. WHAT IS KNOWN ALREADY: Genetic disease and chromosomal rearrangement have been known to significantly impact fertility and development. Therefore, preimplantation genetic testing for aneuploidy (PGT-A), monogenic disorders (PGT-M) and structural rearrangements (PGT-SR), a part of ART, has been presented together to minimize the fetal genetic risk and increase pregnancy rate. For patients or their families who are suffering from chromosome abnormality, monogenic disease, unexplained repeated spontaneous abortion or implantation failure, after accepting genetic counseling, they may be suggested to accept detection from more than one PGT platforms about the embryos to avoid some genetic diseases. However, PGT platforms work through different workflows. The high costliness, lack of material and long-time operation of combined PGT platforms limit their application. STUDY DESIGN, SIZE, DURATION: All 188 embryonic samples from 43 families were tested with HaploPGT platform, and most of their genetic abnormalities had been determined by different conventional PGT methods beforehand. Among them, there were 12 families only carrying structural rearrangements (115 embryos) in which 9 families accepted implantation and 5 families had normal labor ART outcomes, 7 families only carrying monogenic diseases (26 embryos) and 3 families carrying both structural rearrangements and monogenic diseases (26 embryos). Twelve monopronucleated zygotes (1PN) samples and 9 suspected triploid samples were collected from 21 families. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: Here, we raised a comprehensive PGT method called HaploPGT, combining reduced representation genome sequencing, read-count analysis, B allele frequency and haplotyping analysis, to simultaneously detect different genetic disorders in one single test. MAIN RESULTS AND THE ROLE OF CHANCE: With 80 million reads (80M) genomic data, the proportion of windows (1 million base pairs (Mb)) containing two or more informative single nucleotide polymorphism (SNP) sites was 97.81%, meanwhile the genotyping error rate stabilized at a low level (2.19%). Furthermore, the informative SNPs were equally distributed across the genome, and whole-genomic haplotyping was established. Therefore, 80M was chosen to balance the cost and accuracy in HaploPGT. HaploPGT was able to identify abnormal embryos with triploid, global and partial loss of heterozygosity, and even to distinguish parental origin of copy number variation in mosaic and non-mosaic embryos. Besides, by retrospectively analyzing 188 embryonic samples from 43 families, HaploPGT revealed 100% concordance with the available results obtained from reference methods, including PGT-A, PGT-M, PGT-SR and PGT-HLA. LIMITATIONS, REASON FOR CAUTION: Despite the numerous benefits HaploPGT could bring, it still required additional family members to deduce the parental haplotype for identifying balanced translocation and monogenic mutation in tested embryos. In terms of PGT-SR, the additional family member could be a reference embryo with unbalanced translocation. For PGT-M, a proband was normally required. In both cases, genomic information from grandparents or parental siblings might help for haplotyping theoretically. Another restriction was that haploid, and diploid resulting from the duplication of a haploid, could not be told apart by HaploPGT, but it was able to recognize partial loss of heterozygosity in the embryonic genome. In addition, it should be noted that the location of rearrangement breakpoints and the situation of mutation sites were complicated, which meant that partial genetic disorders might not be completely detected. WIDER IMPLICATIONS OF THE FINDINGS: HaploPGT is an efficient and cost-effective detection platform with high clinical value for detecting genetic status. This platform could promote the application of PGT in ART, to increase pregnancy rate and decrease the birth of children with genetic diseases. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by grants from the National Natural Science Foundation of China (81873478, to L.H.), National Key R&D Program of China (2018YFC1003100, to L.H.), the Natural Science Foundation of Hunan Province (Grant 2022JJ30414, to P.X.), Hunan Provincial Grant for Innovative Province Construction (2019SK4012) and the Scientific Research Foundation of Reproductive and Genetic Hospital of China International Trust & Investment Corporation (CITIC)-Xiangya (YNXM-201910). Haplotyping analysis has been licensed to Basecare Co., Ltd. L.K., Y.M., K.K., D.Z., N.L., J.Z. and R.D. are Basecare Co., Ltd employees. The other authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A.